The Proposed Changes for DSM-5 for SLD and ADHD: International Perspectives—Australia, Germany, Greece, India, Israel, Italy, Spain, Taiwan, United Kingdom, and United States. (January 2013) - Al-Yagon, Michal; Cavendish, Wendy; Cornoldi, Cesare; Fawcett, Angela J.; Grünke, Matthias; Hung, Li-Yu; Jiménez, Juan E.; Karande, Sunil; van Kraayenoord, Christina E.; Lucangeli, Daniela; Margalit, Malka; Montague, Marjorie; et al.
This article presents an international perspective of the proposed changes to the DSM-5 for learning disabilities (LD) and attention-deficit/hyperactivity disorders (ADHD) across ten countries: Australia, Germany, Greece, India, Israel, Italy, Spain, Taiwan, the United Kingdom, and the United States. We provide perspectives of the present situation for youth with LD and youth with ADHD and describe the legislation, prevalence rates, and educational systems that serve students with disabilities in the respective countries. We also present a discussion of the expected impact of the proposed changes for the diagnosis of LD and ADHD in each country.